Implikasi Kebijakan Moneter Pada Pasar Modal Indonesia - Martin Luter Purba; Jusmer Sihotang; Nancy Nopeline; Dameria Sofyana Br Napitupulu (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study investigates how inflation shocks, benchmark interest rates, stock transactions, and constant price GDP affect the Indonesian Composite Stock Price Index (IHSG) from 2013 to 2023. The results show that inflation has a permanent negative effect on the IHSG, while constant price GDP increases have a positive effect. Inflation affects GDP in the long run, with a decline after the fourth period, while shocks to stock transactions have a smaller impact on changes in the benchmark interest rate. On the other hand, the impact of the benchmark interest rate fluctuates, with short-term effects on the JCI. To maintain stock market stability and Indonesia's economic growth, this research emphasizes the importance of monetary policy that is responsive to economic shocks. These results provide policymakers and investors with insights to respond to market dynamics.